STUDY OF FINITE DIFFERENCE METHOD IN HEAT FLOW SIMULATION OF TWO-CHAMBER THERMOS SEPARATOR MADE OF POLYPROPYLENE USING MATLAB APPLICATIONS - Pandriana, Aap; Pudjiwati, Sri; Alva, Sagir; Tarigan, Kontan; Sudarma, Andi Firdaus; Khaerudini, Deni Shidqi (Universitas Mercu Buana, 2024)
Heat transfer can be defined as transfer of energy from one area to another as a result of temperature differences in objects. This indicates heat transfer not only explains how heat energy is transferred from one object to another, but can also predict the rate of heat transfer that occurs under certain conditions. In this case, what is related to the heat flow model equation is two-chamber thermos separator where the separator is made of polypropylene. This separator functions to prevent the flow of heat from one side to the other side of the thermos tube. Polypropylene is included in the insulator category, although heat transfer still occurs. The heat transfer will be calculated using the finite difference method in parabolic partial differential equations using the Matlab application. The heat transfer process is assumed to occur by conduction, with a separator length of 1 cm. Assume the first side of the divider has a right temperature of 100°c, and the other side 20°c. The temperature point measured on the separator is located in the center of the separator. After completing the solution using the Matlab application with the finite difference method, a heat transfer flow simulation was obtained in the two-chamber thermos separator which shows the heat flow transfer at any time. At 0.1 seconds the temperature at T1 is 2.4°c, while at 10 seconds is 65.9704°c. Then at 0.1 seconds the temperature at T4 is 0.48°c, while at 10 seconds 19.5436°c. The conclusion is in the separator of the two-chamber thermos there is significant heat flow from the side of the first tube to the other side.